Inculcating professionalism among medical students: experience of the International University Malaysia - Osman, Ariff (Eubios Ethics Institute, 2010)
Training medical professionals requires thorough planning through well-thought medical curriculum that takes into account the changes surrounding the profession itself and the expectation of the community with regard to the graduate that it intent to produce. The Kulliyah (faculty) of Medicine, International Islamic University Malaysia, (IIUM) pioneered what it called, Islamic Input Medical Program (IIMP) since its inception in 1995, in its effort to produce a different ʻbreedʼ of doctors who not only excel in their professional duty but also portray conduct, (akhlaq) expected of a good Muslim. A good Muslim doctor is expected to portray a highest degree of medical professionalism and demonstrate proper etiquette while dealing with his/her patients. However, inculcating professionalism and proper etiquette among medical undergraduates is not an easy matter. Learning this value could be done through a workshop activity whereby students demonstrate their understanding on these aspects of care through discussion of case studies given to them prior to the scheduled activity. Although it is difficult to measure and assess the degree of understanding and practice of professionalism among students, a portfolio seems to be a promising learning and teaching tool to assess the studentʼs achievement as specified in the learning outcome. This article describes our experience in trying to develop such attitude among our medical students.